COVID-19: Sports activity and health-related quality of life of Swiss children and adolescents before and during the initial stay at home period. (April 2023) - Zehnder, Cäcilia; Nigg, Claudio R; Benzing, Valentin
The aim of this study was to investigate sports activity and health-related quality of life (HRQoL) of Swiss children and adolescents (7–16 years) during the national COVID-19 stay at home (SaH) period. In total, 237 parent-child pairs gave information about HRQoL and sports activity (duration and type) before and during SaH. Results show that sports activity decreased during SaH and was also positively related to HRQoL. These findings indicate that sports activity of children and adolescents should be promoted during SaH, for which innovative home-based interventions may be useful.